Positive Psychology, Well-Being, and Mindfulness: A Successful Partnership Towards the Development of Meaningful Tourist Experiences - Câmara, Ester; Pocinho, Margarida; Agapito, Dora; Neves de Jesus, Saul (Journal of Tourism, Sustainability and Well-being, 2022)
Tourism is going through a very challenging phase due to the current pandemic situation. In this context, psychology and tourism are a successful partnership to develop meaningful experiences considering tourists’ needs, desires, and expectations. This interconnection is observed through the application of positive psychology in the context of meaningful tourist experiences. This approach comprises adequate indicators to explore the tourism field from the perspective of individuals’ well-being. Positive psychology, positive tourism, well-being, and mindfulness constitute the theoretical foundations of this article, which intends to understand how they are intertwined to fulfil one goal: developing meaningful tourist experiences. This article offers a theoretical reflection on the connections between the referred theoretical foundations. In so doing, it proposes a preliminary diagram illustrating the theoretical links observed in literature, which acts as a first step towards the design of a systematic literature review on the antecedents and outcomes of meaningful tourist experiences.